(untitled) (CAHIERS MAGELLANES-NS, 2024)
Spice leaves, such as Bay Leaf, hold multifaceted importance in daily life, serving as essential ingredients in cooking and, notably, emerging as potential remedies during the COVID-19 pandemic. However, challenges arise in spice leaf farming due to manual cultivation methods, hindering disease detection. To tackle this, a survey employing transfer learning with InceptionV3 architecture for image classification was conducted, distinguishing between healthy and diseased leaves. This innovative approach facilitates efficient disease identification, aiding farmers in maintaining crop quality and yield. By leveraging advanced technologies like convolutional neural networks, farmers can swiftly detect and address diseases, ensuring the continued availability of high-quality spice leaves for culinary and medicinal purposes.